Site‐Selective Catalytic C(sp2)H Bond Azidations1. Issue 26 (9th May 2013) - Song, Weifeng; Kozhushkov, Sergei I.; Ackermann, Lutz
<x xml:space="preserve">Abstract</x> Inexpensive copper(I) catalysts allow the direct site‐selective azidation (CN bond formation) of C(sp2)H bonds in electron‐rich heteroarenes and readily available anilines (see scheme). The reaction occurs under remarkably mild conditions and has a broad substrate scope.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>